WEED MANAGEMENT IN KHARIF GRAIN SORGHUM (SORGHUM BICOLOR) - P. SUJATHAMMA (The Bioscan, 2015)
A field study was conducted at Regional Agricultural Research Station, Palem during kharif 2013 on weed management of grain sorghum. The experiment comprising of ten weed control treatments of pre and post- emergence herbicides along with weed free and weedy check was conducted in Randomized Block Design with three replications on sandy clay loam soil with P H 8.07. The experimental field was infested with Cynodon dactylon, Dactylactenium aegypticum, Digitaria sanguinalis, Cyperus rotundus, Celosia argentea, Dinebra retroflexa, Ageratum conyzoides, Commelina benghalensis, Digera arvensis, Parthenium hyisterophorus and Phyllanthus niruri. The weed free check recorded significantly highest grain (2843 kg/ha) and stover (7624 kg/ha) yields. However, grain yield was remained at par with pre- emergence application of Atrazine @ 0.5 kg a.i./ ha followed by two hand weedings at 30 and 45 DAS(T 2 ) and pre-emergnece application of Atrazine @ 0.25 kg a.i./ha + Pendimethalin @ 0.25 kg a.i./ha (Tank mixed) +2,4- D @ 0.5 kga.i./ha as post- emergnece at 30DAS(T 7 ). Among the herbicidal treatments, pre- emergence application of Atrazine @ 0.5 kg a.i./ha followed by two hand weedings at 30 and 45 DAS recorded significantly lower grassy weed density (3.32/m 2 ), highest weed control efficiency (83%) at 60 DAS and the lowest weed index (5.7%).